Surgical team communication and compliance in implementing surgical safety checklist - Muji Rahayu; Ahmad Nur Khoiri; Rodiyah; Eka Mei Dianita; Tukimin (Journal of Clinical Nursing Studies and Practice, 2025)
Poor team communication is the most common cause of side effects in all aspects of health care. Non-compliance with the implementation of the surgical safety checklist is a form of poor team communication that can cause harm to patient safety. The purpose of this study was to determine the relationship between surgical team communication and compliance with the implementation of the surgical safety checklist. The research design used was a correlative analytical study with a cross- sectional approach with a total sampling technique with 42 respondents. The statistical test used in this study was the Spearman rank. The results showed that almost all respondents had good communication, and almost all respondents were compliant in implementing the SSC filling. From the results of the statistical test using Spearman's rank analysis H1 was accepted, which means that there is a relationship between surgical team communication and compliance with the implementation of the surgical safety checklist. The results of this study can be input if the team communication support is good, then compliance in the implementation of SSC filling will also increase. It is expected that IBS nurses can improve team communication by complying with the implementation of SSC filling.